IMPLEMENTASI MIND MAPPING PADA PEMBELJARAN TEMATIK KELAS VI SD NEGERI 1 GUNUNGREJO - Rosidah Nur Rohmah; Muhammad Sulistiono; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
In the learning process carried out by educators, it can also be seen from the teaching they apply to students. Many educators use methods that make them more understandable about their teaching, and also still use the old method because they are still using the old teaching. Based on the description presented, the researcher wants to conduct a research entitled